Taxpayer Awareness as a Mediating Factor in Tax Socialization, Tax Sanctions, and Taxpayer Compliance (Case Study: KPP Pratama South Cikarang, Bekasi Regency) - Hajar Mayang Lenggang Pakuan; Apollo Daito (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research aims to analyze the effect of tax socialization No. 44 of 2020, tax sanctions and taxpayers knowledge on Taxpayer Compliance. In addition, this study also analyzes taxpayer awareness as a variable that mediates the effect of tax socialization, tax sanctions, and taxpayer knowledge on taxpayer compliance. This research uses quantitative methods. The type of data used in this research is primary data with questionnaire method. Total The number of samples obtained as many as 310 taxpayers. Analysis and hypothesis testing using SmartPls 3.0. The results show that tax socialization No.44 of 2020 has no effect on taxpayer compliance, tax sanctions have no effect on taxpayer compliance, but taxpayer knowledge has a significant effect on taxpayers, also taxpayer awareness as a mediating variable has a significant effect on taxpayer compliance. For the results of the indirect analysis through the mediating variable, it shows that tax awareness does not mediate the effect of tax socialization on taxpayer compliance, taxpayer awareness does not mediate tax sanctions on taxpayer compliance, but taxpayer awareness significantly mediates taxpayer knowledge on taxpayer compliance.